Abrasion properties of self-suspended hairy titanium dioxide nanomaterials - Zhang, Jiao-xia; Liu, Si; Yan, Chao; Wang, Xiao-jing; Wang, Lei; Yu, Ya-ming; Li, Shi-yun (Applied nanoscience, 2017)
Considering the excellent solubility of pyrrolidone ring organic compounds, the synthesized N -(trimethoxysilyl) propyl- N -methyl-2-pyrrolidone chlorides was tethered onto titanium dioxide (TiO 2 ) nanoparticles to improve dispersion of TiO 2 , and then polyethylene oxide (PEO) oligomer through ion exchange embraced the tethered TiO 2 to obtain a novel self-suspended hairy TiO 2 nanomaterials without any solvent. A variety of techniques were carried out to illustrate the structure and properties of the self-suspended hairy TiO 2 nanomaterials. It was found that TiO 2 nanoparticles embody monodispersity in the hybrid system though the “false reunion” phenomenon occurring due to nonpermanent weak physical cross-linking. Remarkably, self-suspended hairy TiO 2 nanomaterials exhibit lower viscosity, facilitating maneuverable and outstanding antifriction and wear resistance properties, due to the synergistic lubricating effect between spontaneously forming lubricating film and nano-lubrication of TiO 2 cores, overcoming the deficiency of both solid and liquid lubricants. This make them promising candidates for the micro-electromechanic/nano-electromechanic systems (MEMS/NEMS).